Uma técnica baseada em eventos para rastreabilidade entre requisitos modelados com SysML - Jesus, Telmo Oliveira de (2017)
Managing a software project is an increasingly complex task as it demands the quality of the final product to increase. Thus, e ective management is required from project design to software deployment and maintenance. According to the literature found, Requirements Engineering is the most important phase in terms of final impact on a software project. Changes in software requirements occur throughout the software process, from elicitation and requirements analysis to software operation. Requirements traceability enables one to identify the source and the dependency among software requirements. Studies show that current requirements traceability tools and methods are insu cient which makes it di cult to use traceability in practice. The goal of this work was the proposal of a requirements traceability technique combined with a modeling language and supported by a tool. To achieve this goal, bibliographic review, state-of-the-art research, comparative analysis, questionnaire and interviews were used as research instruments. Initially, an analysis of requirements traceability techniques and evaluation of requirements traceability tools were performed to evaluate if the techniques are used in practice and are being supported by software tools. After these analysis, an event-based traceability technique was proposed using concepts from the SysML modeling language. A software tool was developed to support this technique. Whenever a requirement is modified, the tool notifies stakeholders of such change made to the system requirements through e-mail. The technique and the tool were evaluated by twenty four information technology professionals using a questionnaire based on the TAM model that encompasses the concepts of perceived utility, perceived ease of use and perceived use, and interviews. As a result, the lack of relationship between the techniques and the tools surveyed was observed, and the criterion of automatic communication with stakeholders was not addressed in any evaluated tool. With regard to the proposed technique and tool, a wide acceptance of technique and tool was observed. The acceptance of the proposals was carried out by professionals with varied experiences in software development.